Tafsir The Concepts Of Sakinah, Mawaddah, and Rahmah As Pillars of Muslim Family Resilience: A Study of Qur’an Surah Ar-Rum [30]: 21 - M. Safar Gani; Hartawan Hartawan; Ilham Maulidin (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD, 2025)
The family is the most fundamental social institution shaping the moral, and spiritual well-being of society; therefore, strengthening family resilience is crucial in responding to modern challenges such as marital conflict, rising divorce rates, and declining quality of family communication. This study aimed to analyze the concepts of sakinah, mawaddah, and rahmah as the core foundations of Muslim family resilience based on QS. Ar-Rum [30]:21. The research employed a descriptive qualitative method using the thematic exegesis (tafsir maudhu’i) approach, combined with literature review of the Qur’an, both classical and contemporary tafsir, as well as relevant modern research on family resilience. The results revealed that sakinah contributes to psychological stability, mawaddah strengthens emotional bonding, while rahmah fosters compassion and protection that are essential for resilient families. The discussion indicated that these values remain highly relevant for addressing contemporary family issues, including emotional conflict, economic pressures, and digital disruption. The novelty of this study lay in integrating Qur’anic concepts with the theory of family resilience to formulate a spiritually based model of family strength. These findings implied the need for policy development in family empowerment programs that emphasize balanced emotional, spiritual, and social reinforcement.